2018
DOI: 10.5230/jgc.2018.18.e24
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery after Surgery for Gastric Cancer Patients Improves Clinical Outcomes at a US Cancer Center

Abstract: PurposeEnhanced recovery after surgery (ERAS) protocols for gastric cancer patients have shown improved outcomes in Asia. However, data on gastric cancer ERAS (GC-ERAS) programs in the United States are sparse. The purpose of this study was to compare perioperative outcomes before and after implementation of an GC-ERAS protocol at a National Comprehensive Cancer Center in the United States.Materials and MethodsWe reviewed medical records of patients surgically treated for gastric cancer with curative intent fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Minimally invasive surgery has been widely used and several studies, including randomized trials have demonstrated the higher efficacy of laparoscopic and robot-assisted surgeries compared to open surgery [163164]. Anesthesia techniques and perioperative nutritional support have enhanced postoperative recovery after the guidelines for gastric cancer surgery were published [165166]. Laboratory and immune parameters are reported to be a predictor of outcomes in several studies, including our earlier studies [3101115].…”
Section: Inflammation and Gastric Cancermentioning
confidence: 99%
“…Minimally invasive surgery has been widely used and several studies, including randomized trials have demonstrated the higher efficacy of laparoscopic and robot-assisted surgeries compared to open surgery [163164]. Anesthesia techniques and perioperative nutritional support have enhanced postoperative recovery after the guidelines for gastric cancer surgery were published [165166]. Laboratory and immune parameters are reported to be a predictor of outcomes in several studies, including our earlier studies [3101115].…”
Section: Inflammation and Gastric Cancermentioning
confidence: 99%
“…In a subsequent randomized trial, shorter hospital stay has also been demonstrated in an enhanced recovery group (median 10 days vs. 9 days, p= 0.037) (31). Besides, in a recent study from the United States, the ERAS group has demonstrated shorter hospital stay with a mean difference of 2.3 days (mean 7.8 ± 3.6 days vs. 5.5 ± 2.0 days, p= 0.010) (18). The only study that showed that the ERAS program did not affect the length of hospital stay was the study published in Japan in 2012 (32).…”
Section: Discussionmentioning
confidence: 90%
“…However, gastrectomy for gastric cancer remains a high-risk procedure with significant morbidity and mortality (13,14). Clinical pathway has also been used for gastric cancer surgery, and studies have demonstrated improvement in peri-operative outcomes (15)(16)(17)(18). Enhanced Recovery After Surgery (ERAS) protocol is an evidence-based model of standardized clinical pathway system, which has been considered safe and effective in a recent meta-analysis in gastrectomy for gastric cancer patients (19).…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced Recovery After Surgery (ERAS) programs are evidence-based, multidisciplinary, surgical care pathways developed to expedite recovery and improve patient outcomes after elective surgery (Desiderdio et al 2018 ; McConnell et al 2018 ; Brown et al 2018 ; Ban et al 2019 ). ERAS, comprised of several specific, evidence-based protocols, allows for the standardization of surgical patient care preoperatively, intraoperatively, and postoperatively.…”
Section: Introductionmentioning
confidence: 99%